219k views
6 votes
Complete the inequality.
(-9/8)/(-2 3/4) ? 3/22
>
<
=

Complete the inequality. (-9/8)/(-2 3/4) ? 3/22 > < =-example-1
Complete the inequality. (-9/8)/(-2 3/4) ? 3/22 > < =-example-1
Complete the inequality. (-9/8)/(-2 3/4) ? 3/22 > < =-example-2
User EvanDotPro
by
4.9k points

1 Answer

6 votes

Answer:

(-3/8)/(-2 3/4) = 3/22

Explanation:

Solve the following;


(\left(-(3)/(8)\right))/(\left(-2(3)/(4)\right))


=(\left(-(3)/(8)\right))/(\left(-(11)/(4)\right))


\mathrm{Apply\:the\:fraction\:rule}:\quad (-a)/(-b)=(a)/(b)


=((3)/(8))/((11)/(4))


\mathrm{Apply\:the\:fraction\:rule}:\quad ((a)/(b))/((c)/(d))=(a\cdot \:d)/(b\cdot \:c)


=(3\cdot \:4)/(8\cdot \:11)


(3)/(22)

Thus,
(\left(-(3)/(8)\right))/(\left(-2(3)/(4)\right)) =
(3)/(22)

~Learn with lenvy~

User Ketan Ghumatkar
by
4.8k points